PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS EDUCAPLAY PADA MATERI NORMA DALAM KEHIDUPAN UNTUK MURID KELAS V SDN BANJARSAWAH 1 - Rafilia Tamar Hilwa; Faridahtul Jannah; Ryzca Siti Qomariyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The goal of this study was to develop Educaplay-based interactive learning resources on everyday norms for fifth-grade students at SDN Banjarsawah 1 and evaluate their effectiveness, validity, and usefulness. The development of this learning resource was motivated by the need for instructional resources that might help students understand abstract concepts of commonplace standards through engaging, interactive, and contextual learning activities. The research and development (R&D) technique for this study followed the five steps of the ADDIE model: analysis, design, development, implementation, and evaluationThe study's subjects were fifth-grade students from SDN Banjarsawah 1. Among the instruments used to collect data were learning outcome evaluations, teacher and student response questionnaires, media expert validation sheets, and material expert validation sheets. The results show that the Educaplay-based interactive learning materials were rated as extremely valid with a media expert validation score of 96.88% and as valid with a material expert validation score of 87.50%. A very valid category was indicated by the average product validation score of 92.19%. With a score of 93.75%, teacher replies were classified as extremely practical. In the meantime, the effectiveness test revealed a 92% student learning mastery percentage, which was classified as extremely effective. These results show that using the created Educaplay-based interactive learning materials to teach Pancasila Education about everyday norms is viable. In summary, the Educaplay-based interactive learning materials created for this study satisfied the requirements of being highly effective, highly practical, and highly valid. As a result, it might be utilised as a substitute teaching tool to help educators and learners comprehend social standards in a more interesting, participatory, and significant method.